Immunoexpression of growth factors and receptors in polymorphous low-grade adenocarcinoma - Garcia Rosa, Ana Claudia; Soares, Andresa Borges; Santos, Fabricio Passador; Furuse, Cristiane [UNESP]; Araujo, Vera Cavalcanti de (Wiley-Blackwell, 2016)
BACKGROUND: Polymorphous low-grade adenocarcinoma (PLGA) is a rare malignant tumor that usually arises in the minor salivary glands. Growth factors are cell-secreted peptides that regulate biological processes such as growth, proliferation, and differentiation. In salivary gland tumors, immunoexpression of growth factors and their receptors is associated with cell proliferation, malignant transformation, and tumor invasion. This study analyzed the expression of growth factors and receptors in PLGA, in other to better understand the mechanisms involved in the process of neoplastic cell proliferation and tumor progression. METHODS: The expression of growth factors FGF-2, PDGF-A, PDGF-B and receptors FGFR-1, FGFR-2, PDGFR-a, and EGFR was analyzed in 24 PLGA samples in comparison with normal salivary glands, by immunohistochemistry. A semi-quantitative analysis determined cell positivity in all stained sections. Scores were assigned according to percentage of reactive cells: score 0 < 10%; score 1-10 to 25%; score 2-25% to 50%; score 3- > 50%. The level of significance was set at 5%. RESULTS: Most of the growth factors and receptors, apart from FGFR-2, were significantly reactive in PLGA. Comparing to salivary acini, all of the reactive growth factors and receptors were significantly stronger in PLGA. Comparing to salivary ducts, the expression of FGF-2, PDGF-B, FGFR-1, and EGFR was significantly stronger in the nuclei and/or cytoplasm of the neoplastic cells. CONCLUSIONS: The increased expression of the growth factors and receptors in the PLGA, compared to normal salivary glands, may be related to cell proliferation, somehow participating in the oncogenic process.
Keywords: EGFR; FGF; growth factors; PDGF; Polymorphous low-grade adenocarcinoma; salivary glands